The Use Of Top-Down Approach In Teaching Listening Through Short Stories - Budi Kadaryanto; C. J. Aryanti Cori (Universitas Bandar Lampung, 2011)
Listening comprehension is the first skill that students should master, because before someone understands and starts to speak, lie or she has to hear sounds, words, or speech pattern. Listening is considered as a difficult language skill since it involves some aspects of the language, for example, vocabulary, understanding the sound, grammar, getting, the mainL_ understandingidea, specific information and reference. The teaching of listening in formal schools is still considered unsuccessful for that it tends to make students boring. Therefore, English teachers should provide more challenging and interesting listening activities. Teaching listening withZ7short stories is said to be one of the way to reduce students boredom and to increase students listening comprehension.For the above reasons, this research was intended to find out whether there was significant improvement of students listening comprehension in short stories after being taught through top - down approach. This research was done in a group pretest posttest design. The population of this research was the eleventh grade in SMA YP UN ILA Bandar Lampung. The sample of this research was XI IPA I and was selected by using random sampling technique. In collecting the data, the researcher administered the pretest, the treatments and posttest. The data was analyzed by using repeated measure t-test. In which the significance was determined by p<0.05. The result of t-test computation showed that (-ratio was higher than t-table (t,>t,.J, that is, (29.330>2.021), it can be concluded that there was a significant improvement of students listening comprehension after being taught short stories through top - down approach. This means that teaching listening through short stories in a top-down approach was applicable to improve sttideiitslistening omprehension ability.